MANAJEMEN EKSTRAKURIKULER DALAM MENINGKATKAN MINAT BAKAT PESERTA DIDIK (STUDI KASUS di SMA INSAN KAMIL TARTILA, TANGERANG) - Sunan Sukmanagara; Lukman Hakim (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study discusses the important role of extracurricular management in increasing the interests and talents of students in the educational environment. Extracurricular activities are activities outside the main curriculum that can facilitate the development of students' potential in various fields. The purpose of this study was to analyze effective strategies and methods in extracurricular management to increase students' interests and talents. This research was conducted using qualitative methods. Data was collected through interviews, observations, and questionnaires given to students, supervising teachers, and extracurricular managers. This research has implications for schools and education policy makers to pay more attention to extracurricular development and management. In conclusion, extracurricular management plays an important role in exploring the potential interests and talents of students in the educational environment. By providing a variety of extracurricular activities that are directed and involve active support from supervising teachers and administrators, schools can become an inspiring place to develop the potential of students holistically.